Periodontitis and Glycaemic Dyscontrol Substantially Increase the Risk of Medication-Related Osteonecrosis of the Jaw: A Preclinical Study in Female Rats - João Martins de Mello-Neto; Luan Felipe Toro; Letícia Chaves Ferreira; Vinícius Franzão Ganzaroli; Leandro Lemes da Costa; Rodrigo Isaías Lopes Pereira; Arthur Michellim Kirasuke; Ana Beatriz Carreto; Isabella Zacarin Guiati; Valdir Gouveia Garcia; Letícia Helena Theodoro; Edilson Ervolino (Journal of Clinical Medicine, 2026)
Background/Objectives: There is limited understanding of how periodontitis progresses in individuals with diabetes who are undergoing antiresorptive drug therapy, particularly given that both are risk factors for medication-related osteonecrosis of the jaw (MRONJ). This study evaluated the effect of therapy with an oncological dose of zoledronate on the progression of experimental periodontitis (EP) in diabetic female rats. Methods: One hundred and eight female rats (12 months old) were assigned to four groups: VEH-NG (n = 26), VEH-DM (n = 28), ZOL-NG (n = 26) and ZOL-DM (n = 28). VEH-NG and VEH-DM groups received 0.45 mL of vehicle, and ZOL-NG and ZOL-DM groups received 0.45 mL of zoledronate (100 μg/kg). Treatment with vehicle or zoledronate was administered every three days for seven weeks. At week 0, a cotton ligature was placed around the right and left mandibular first molars to induce experimental periodontitis (EP). In week 2, VEH-DM and ZOL-DM groups were subjected to an injection of streptozotocin into the caudal vein to induce diabetes mellitus (DM). VEH-NG and ZOL-NG groups received sodium citrate buffer via the same route. Euthanasia was performed 14, 21, and 35 days after ligature placement. Microtomographic, histomorphometric, and immunohistochemical analyses (TNFα, IL-1β, and TRAP) were performed. Results: The percentage of non-vital bone tissue, local inflammation, and TNFα and IL-1β immunolabelling in the furcation region were higher in ZOL-NG and even higher in ZOL-DM. Alveolar bone loss and the number of TRAP-positive cells were lower in the groups treated with zoledronate. Conclusions: During treatment with an oncological dose of zoledronate, periodontitis and glycaemic dyscontrol substantially increase the risk of MRONJ.